1988
DOI: 10.5271/sjweh.1942
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exposure to Freon 11, 1,1,1-trichloroethane or perchloroethylene on the lipid and fatty-acid composition of rat cerebral cortex.

Abstract: Effects of exposure to Freon 11, 1,1,1-trichloroethane or perchloroethylene on the lipid and fatty-acid composition of rat cerebral cortex. by Kyrklund T, Kjellstrand P, Haglid KG Affiliation: Institute of Neurobiology, University of Goteborg, Sweden.This article in PubMed: www.ncbi.nlm.nih.gov/pubmed/3387963Effects of exposure to Freon 11, 1,1,1-trichloroethane or perchloroethylene on the lipid and fatty-acid composition of rat cerebral cortex by Titus Kyrklund , PhD,1 Per Kjellstrand , PhD,2 Kenneth G Haglid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0
1

Year Published

1990
1990
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 10 publications
(11 reference statements)
1
16
0
1
Order By: Relevance
“…while it was changed to 1280 the last day of exposure. At the end of the experimental period all animals were decapitated, their brains being removed and dissected as previously described (Kyrklund et al 1988). Six animals in each group were subjected to analyses of lipid composition and fatty acid pattern.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…while it was changed to 1280 the last day of exposure. At the end of the experimental period all animals were decapitated, their brains being removed and dissected as previously described (Kyrklund et al 1988). Six animals in each group were subjected to analyses of lipid composition and fatty acid pattern.…”
Section: Methodsmentioning
confidence: 99%
“…Lipid and fatty acid determinations were performed as previously described (Kyrklund 1987;Kyrklund et al 1988). The fatty acid methylesters of total ethanolamine phosphoglycerides (EPG) were analysed by capillary-gas-chromatography on a DB-23 column (J & W Scientific, U.S.A.) of 30 m length and 0.53 mm 0 The analysis was started at 165" for 5 min.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Altered brain neurochemistry: There are no studies in humans measuring brain neurochemistry after exposure to perc, in either children or adults. In experimental studies, altered brain neurochemistry has been observed after gestational exposure to rats (Nelson et al, 1979) and guinea pigs (Kyrklund and Haglid, 1991), as well as after adult exposure to rats (Honma et al, 1980a,b;Kyrklund et al, 1988Kyrklund et al, , 1990Savolainen et al, 1977;Wang et al, 1993) and gerbils (Karlsson et al, 1987;Kyrklund et al, 1984Kyrklund et al, , 1987Rosengren et al, 1986). These studies do not necessarily indicate increased effects on brain neurochemistry after gestational exposure compared to adult exposure.…”
Section: Postnatal Outcomesmentioning
confidence: 99%